IL-33 Participates in G. Vaginalis-Induced Bacterial Vaginosis: Involvement of Intravaginal IgA - Zhou M; Zhou L; Liu J; Yu S (Journal of Inflammation Research, 2025)
Min Zhou,1 Lili Zhou,2 Junbo Liu,1 Shaohui Yu1 1Department of Gynecology, Changchun University of Chinese Medicine Affiliated Hospital, Changchun, Jilin, People’s Republic of China; 2Department of Obstetrics, Changchun University of Chinese Medicine Affiliated Hospital, Changchun, Jilin, People’s Republic of ChinaCorrespondence: Shaohui Yu, Department of Gynecology, Changchun University of Chinese Medicine Affiliated Hospital, Changchun, Jilin, 130000, People’s Republic of China, Email yush@ccucm.edu.cnIntroduction: Bacterial vaginosis (BV) is a common gynecological disease characterized by an abnormal increase in vaginal secretions, odor and itching. The pathogenesis of BV is not fully understood, but it is believed that the disruption of the mucosal immune system plays a key role. We investigated the role of IL-33 in preventing BV and explored the mechanism by which IL-33 regulates intravaginal IgA.Methods: Protein levels of IL-33 and IgA, and the pH value of vaginal secretions in healthy donors and patients with BV (14 vs 14) were determined by ELISA. G. vaginalis-induced bacterial vaginosis mouse model was established using wild-type (WT) and IL-33 knockout (KO) mice. Protein levels of IL-33, IgA and TGF-β, the pH value of vaginal secretions, and Gram-staining were measured in vivo and in vitro to investigate the role of IL-33 in BV progression.Results: IL-33 and IgA were significantly decreased in vaginal secretions of patients with BV. IL-33 deficiency aggravated BV induced by G. vaginalis in a mouse model, while IL-33 supplementation prevented it. IL-33 modulated intravaginal IgA expression through the TGF-β signaling pathway in B cells.Conclusion: IL-33 prevents G. vaginalis-induced BV by modulating intravaginal IgA expression through the TGF-β signaling pathway in B cells.Keywords: bacterial vaginosis, G. vaginalis, IL-33, IgA, TGF-&#x03B2